Comparing Drivers Cultural Sensitivity Value between Gojek and Goviet from Digital Ads - Natasia Angreani; Samantha Tandranegara; Rustono Farady Marta; Changsong Wang (Universitas Ahmad Dahlan, 2021)
Gojek is one of the multi-service technology platforms co-founded by native Indonesian. In their eight-year, Gojek expands its service to other markets in Vietnam. Although Indonesia and Vietnam are both located in the Southeast Asian region and have the same climate with the majority of the citizens who work as farmers and fishers, Indonesia and Vietnam certainly have a series of differences such as language,Â Â culture, and religion. This study explores the intercultural sensitivity of Gojek drivers who went to Vietnam to meet fellow Goviet drivers. Together, they enjoy the beauty of the country and experience Vietnamese culture, which is shown in the GO-INTERNATIONAL YouTube video. This study used Bannettâ€™s theory of the Developmental Model of Intercultural Sensitivity (DMIS) by the content analysis method to analyze the intercultural sensibility value on the Gojek â€œGO-INTERNATIONALâ€ video. The results indicate four stages such as minimization, acceptance, adaptation, and integration. This ad shows the bonds found in different cultural backgrounds and the ethnorelativism of Gojek drivers towards Goviet drivers.